Performance of Sweet Potato (Ipomea batatas L.) Varieties under North Konkan Conditions of Maharashtra - MALSHE, K.V.; KHANDEKAR, R.G.; MHASKAR, N.V. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
.